Comprehensive spectroscopic, metabolomic, and proteomic liquid biopsy in the diagnostics of hepatocellular carcinoma - Kralova, Katerina; Vrtelka, Ondrej; Fouskova, Marketa; Smirnova, Tatiana Anatolievna; Michalkova, Lenka; Hribek, Petr; Urbanek, Petr; Kuckova, Stepanka; Setnicka, Vladimir (Talanta, 2024)
Liquid biopsy is a very topical issue in clinical diagnostics research nowadays. In this study, we explored and compared various analytical approaches to blood plasma analysis. Finally, we proposed a comprehensive procedure, which, thanks to the utilization of multiple analytical techniques, allowed the targeting of various biomolecules in blood plasma reflecting diverse biological processes underlying disease development. The potential of such an approach, combining proteomics, metabolomics, and vibrational spectroscopy along with preceding blood plasma fractionation, was demonstrated on blood plasma samples of patients suffering from hepatocellular carcinoma in cirrhotic terrain (n = 20) and control subjects with liver cirrhosis (n = 20) as well as healthy subjects (n = 20). Most of the applied methods allowed the classification of the samples with an accuracy exceeding 80.0 % and therefore have the potential to be used as a stand-alone method in clinical diagnostics. Moreover, a final panel of 48 variables obtained by a combination of the utilized analytical methods enabled the discrimination of the hepatocellular carcinoma samples from cirrhosis with 94.3 % cross-validated accuracy. Thus, this study, although limited by the cohort size, clearly demonstrated the benefit of the multimethod approach in clinical diagnosis.
Keywords: jaterní cirhóza; Proteomics; lidé; Liver Neoplasms; nádory jater; spektrální analýza; Carcinoma, Hepatocellular; proteomika; Liquid Biopsy; Liver Cirrhosis; hepatocelulární karcinom; tekutá biopsie; Spectrum Analysis; Humans